Three-Dimensional Numerical Analysis and Engineering Evaluation of Stilling Basin and Foundation Bedrock of Kala Hydropower Station, China - Xu, Jianjun; Cui, Zhihao; Qian, Kun; Sun, Xiang; Xu, Jie (Frontiers in Physics, 2022)
Kala reservoir is a large hydropower station, which will be built on the Yalong River in Sichuan Province, China. The topography and geomorphology at the project area of the hydropower station are characterized by high mountains and a deep V-shaped valley, where the engineering geological conditions are complex. The stilling basin of the Kala reservoir is planned to be built on a weak rock mass called a sericitized slate. Therefore, the safety of stilling basin structure has an important impact on the regular operation of the Kala hydropower station. To evaluate the working state of the stilling basin structure, a three-dimensional numerical model was built, including the valley, mountains and stilling basin structure. FLAC3D (A three-dimensional finite-difference simulation software) was used to simulate engineering and mechanical responses of the stilling basin structure and the foundation rock mass under various working conditions. Based on the simulation results, the structural layout of stilling basin and the rationality of sericitized slate treatment measurements were verified. It was determined that the engineering properties of the sericitized slate would generally meet the engineering requirements. However, considering that the characteristics of sericitized slate are easy to weaken with water, it was suggested to carry out necessary foundation improvement for sericitized slate to strengthen its engineering mechanical properties.